Transcriptomic Profiling of Intracranial Arteries in Adult Patients With Moyamoya Disease Reveals Novel Insights Into Its Pathogenesis - Xu, Shuangxiang; Wei, Wei; Zhang, Feiyang; Chen, Tongyu; Dong, Lixin; Shi, Jichun; Wu, Xiaolin; Zhang, Tingbao; Li, Zhengwei; Zhang, Jianjian; Li, Xiang; Chen, Jincao (Frontiers in Molecular Neuroscience, 2022)
Moyamoya disease (MMD) is a rare, progressively steno-occlusive cerebrovascular disorder of unknown etiology. Here, we revealed the gene expression profile of the intracranial arteries in MMD via the RNA-sequencing (RNA-seq). We identified 556 differentially expressed genes (DEGs) for MMD, including 449 and 107 significantly upregulated or downregulated genes. Compared with atherosclerosis-associated intracranial artery stenosis/occlusion (AS-ICASO) controls, upregulated genes were mainly involved in extracellular matrix (ECM) organization, whereas downregulated genes were primarily associated with mitochondrial function and oxidative phosphorylation in MMD. Moreover, we found that a separate sex analysis uncovers more DEGs (n = 1.022) compared to an combined sex analysis in MMD. We identified 133 and 439 sex-specific DEGs for men and women in MMD, respectively. About 95.6% of sex-specific DEGs were protein-coding genes and 3% of the genes belonged to long non-coding RNAs (lncRNA). Sex-specific DEGs were observed on all chromosomes, of which 95.49 and 96.59% were autosomal genes in men and women, respectively. These sex-specific DEGs, such as aquaporin-4 (AQP4), superoxide dismutase 3 (SOD3), and nuclear receptor subfamily 4 group A member 1 (NR4A1), may contribute to sex differences in MMD. This transcriptomic study highlighted that ECM and mitochondrial function are the central molecular mechanisms underlying MMD, and revealed sex differences in the gene expression in the intracranial arteries, thereby providing new insights into the pathogenesis of MMD.